PENGANGKATAN KOMISARIS INDEPENDEN DALAM MEWUJUDKAN GOOD CORPORATE GOVERNANCE (TATA KELOLA PERUSAHAAN YANG BAIK) PADA PERSEROAN TERBATAS - Nisa Afifa; Abdul Halim Barkatullah; Yulia Qamariyanti (The Juris, 2022)
The goals to be accomplished in this composing are to analyze and criticize the presence of free commissioners in laws and controls and to analyze and criticize whether the presence of autonomous commissioners inside the company can ensure the usage of the standards of Great Corporate Administration. In composing this proposal, the author employments regulating lawful investigate with the nature of investigate, specifically prescriptive research that points to induce proposals approximately what ought to be done to overcome certain issues. Lawful materials are within the frame of essential lawful materials and auxiliary lawful materials gotten from writing thinks about. Processing and analysis of legal materials are carried out by analyzing legal materials from deductive to inductive. The research results are: First. Appointment of Independent Commissioners within the company is mandatory, this has been regulated as in one of the OJK regulations namely Financial Services Authority Regulation Number 33/POJK.04/2014 concerning Directors and the Board of Commissioners of Issuers or Public Companies, Independent Commissioners must exist in Limited Liability Companies classified as Open/Public, especially in PTs that collect or manage public funds. Second. The Independent Commissioner guarantees the implementation of the principles of Good Corporate Governance in the company if the selected Independent Commissioner has competence and experience, in the selection process the Independent Commissioner has applied the principles of Good Corporate Governance and has fulfilled the Fit and Proper Test requirements by company regulations.